Droga polskich kobiet do Parlamentu Europejskiego - Lesiewicz, Elżbieta (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
In 2004, Polish women took part in the elections to the European Parliament for the first time. It was a long road that led them to take seats there. The beginnings of the Polish women’s movement date back to the 19th century when it was closely connected with the struggle for the independence of Poland. It was then that the stereotype of the Polish Mother emerged, the guardian of the hearth and home, and promoter of patriotism. These, among other things, were the social, cultural and political stereotypes that women seeking to increase their presence in public life needed to face up to. Polish women obtained voting rights rela- tively early on, in 1918. Despite their political rights, they did not participate in the political life of interwar Poland on a larger scale. The women’s organizations that emerged after WWII implemented the ideology that was officially propagated in those times, and strictly followed the policies of the authorities. Significant changes in the women’s movement occurred in the 1980s when authentic women’s initiatives formed around the Solidarity movement. At pres- ent, approximately 300 women’s organizations operate in Poland. Polish accession to the European Union has given Polish women an opportunity to intensify their activities in supra- national politics. Polish women took seats in the European Parliament, although their num- bers thus far have been relatively low. During the 6th parliamentary term, out of 54 Polish Members of the European Parliament, 7 were women. In the EP elections held in 2009, 11 Polish women were elected as MEPs. Regardless of this low level of representation, Polish women are very active and resilient and seriously committed to working in European Parlia- mentary structures.
Women in the European Parliament
Keywords: kobiety; aktywność polityczna; Parlament Europejski